Counter terrorism issues : case studies in the courtroom - Castagnera, James (CRC Press, 2024)
"Drawing extensively upon trial transcripts, witness statements, and judicial opinions, the book reviews the events and cases to demonstrate how the criminal justice system has grappled with conflicting facts and countervailing legal rights and responsibilities. Through the words of witnesses, judges, and the attorneys who tried these cases in America's courtrooms, coverage provides important commentary on the historical/political contexts of these events, enabling readers to understand the significance of these infamous attacks on U.S. soil"-- Provided by publisher.
Keywords: Trump, Donald, -- 1946-; Terrorism -- Prevention -- Law and legislation -- United States.; Terrorism -- Prevention -- Law and legislation -- United States -- Cases.; Terrorism -- Law and legislation -- United States -- Cases.; Capitol Riot, Washington, D.C., 2021.; Political violence -- Washington (D.C.); Presidents -- United States -- Election -- 2020.; Contested elections -- United States.; elektronické knihy; electronic books